Monitoring the use of validation of non-formal and informal learning : thematic report for the 2016 update of the European inventory on validation - (:unkn) unknown (Publications Office of the European Union, 2016)
"This thematic report provides an overview of validation monitoring of non-formal and informal learning across Europe. Based on data collected for the European inventory project, the report explores the extent to which data are available on different aspects of validation in different education sectors. The results show a lack of comprehensive national statistics on validation, exacerbated in many countries by a lack of a clear regulatory framework on validation to build up integrated databases of release annual data. A further challenge is the fragmented offer of validation opportunities. Recommendations highlight the need for the collection of data on different aspects of validation take-up. Encouraging new and/or existing working groups, inter-ministerial committees or similar institutions involving stakeholders can help assess how regional or national data could be compiled/improved and used for planning to inform policy developments on validation" (Editor, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2 Europa; Non-formales Lernen; Informelles Lernen; Anerkennung; Europäische Union